Investigating the impact of alpha/beta and LETd on relative biological effectiveness in scanned proton beams: An in vitro study based on human cell lines. Issue 8 (15th May 2020) - Mara, Elisabeth; Clausen, Monika; Khachonkham, Suphalak; Deycmar, Simon; Pessy, Clara; Dörr, Wolfgang; Kuess, Peter; Georg, Dietmar; Gruber, Sylvia
Abstract : Purpose: A relative biological effectiveness (RBE) of 1.1 is commonly used in clinical proton therapy, irrespective of tissue type and depth. This in vitro study was conducted to quantify the RBE of scanned protons as a function of the dose‐averaged linear energy transfer (LETd ) and the sensitivity factor (α/ß)X . Additionally, three phenomenological models (McNamara, Rørvik, and Jones) and one mechanistic model (repair‐misrepair‐fixation, RMF) were applied to the experimentally derived data. Methods: Four human cell lines (FaDu, HaCat, Du145, SKMel) with differential (α/ß)X ratios were irradiated in a custom‐designed irradiation setup with doses between 0 and 6 Gy at proximal, central, and distal positions of a 80 mm spread‐out Bragg peak (SOBP) centered at 80 mm (setup A: proton energies 66.5–135.6 MeV) and 155 mm (setup B: proton energies 127.2–185.9 MeV) depth, respectively. LETd values at the respective cell positions were derived from Monte Carlo simulations performed with the treatment planning system (TPS, RayStation). Dosimetric measurements were conducted to verify dose homogeneity and dose delivery accuracy. RBE values were derived for doses that resulted in 90 % (RBE90 ) and 10 % (RBE10 ) of cell survival, and survival after a 0.5 Gy dose (RBE0.5Gy ), 2 Gy dose (RBE2Gy ), and 6 Gy dose (RBE6Gy ). Results: LETd values at sample positions were 1.9, 2.1, 2.5, 2.8, 4.1, and 4.5 keV/µm. For the cell lines with high (α/ß)X ratios (FaDu, HaCat), the LETd did not impact on the RBE. For low (α/ß)X cell lines (Du145, SKMel), LQ‐derived survival curves indicated a clear correlation of LETd and RBE. RBE90 values up to 2.9 and RBE10 values between 1.4 and 1.8 were obtained. Model‐derived RBE predictions slightly overestimated the RBE for the high (α/ß)X cell lines, although all models except the Jones model provided RBE values within the experimental uncertainty. For low (α/ß)X cell lines, no agreement was found between experiments and model predictions, that is, all models underestimated the measured RBE. Conclusions: The sensitivity parameter (α/ß)X was observed to be a major influencing factor for the RBE of protons and its sensitivity toward LETd changes. RBE prediction models are applicable for high (α/ß)X cell lines but do not estimate RBE values with sufficient accuracy in low (α/ß)X cell lines.